Control of PV-Hydro Micro-Grid with Energy Storage System Controlled Through Bidirectional Converter - Dipesh Bhatta,; Swarup Khadka,; Surendra Pandit,; Indraman Tamrakar, (KEC Journal of Science and Engineering, 2025)
Traditional ELC for MHP system is designed in such a way that it could be used to maintain the speed of the MHP plant in an isolated micro-grid system where the excess of the electrical energy is dumped into the dummy load during lightly loaded condition. But this system seems ineffective and carries the limitations such as waste of the energy during the lightly loaded period, unstable system during the peak load period, system instability during connected with the grid system and so on. Thus, this report aims to suggest a measure for the limitations through the project,” Control of PV-Hydro micro-grid with energy storage system controlled through bidirectional converter”. All the components are designed, calibrated and synchronized with each other using the MATLAB Simulation Software. Initially, PV plant and MHP plant is designed with capacity of 50KW and 100KW respectively. Inside the PV plant inverter and inverter controller is designed in such a way that is always produces the 400V across the output terminal despite the variation in Temperature and the Irradiation. There by implementing the MPPT (Perturbation and observation (P&O)) algorithm we were able to design the PV System Next, is we have designed the MHP plant that produces the 100KW power at 400V whose excitation and rotor speed is maintained throughout the operation at any load condition. The bidirectional converter with the battery backup system is responsible for maintaining the rotor stability at any load condition i.e. either lightly loaded or heavily loaded condition. The main aim of this project is designing a system where the system will store the excess of the energy in the battery during the lightly loaded condition while maintaining the rotor stability whereas the system will then again act as a source during the peak period when the PV-Hydro system is unable to meet the load demand.